Splenectomy for isolated splenomegaly; experience with twelve patients - Al Saffar, Ahmed A .; Abbas, Mohammed S.; Mohammed, Mazin A. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Changes in the indication for splenectomy in hematology, especially in hematological malignancies, has been observed in the last 10 – 15 years. Yet splenectomy, as a diagnostic tool, is still an option in the management of isolated splenomegaly. Objectives: to describe the outcome of diagnostic splenectomy in the management of 12 patients presenting with isolated splenomegaly. Patients and methods: Between August 2005 and July2012, Twelve patients underwent splenectomy for diagnostic purposes in the hematology unit / Baghdad Teaching Hospital. Analysis of these patients was done with a median follow up of 16 months (6 months -4 years). Results: The median age was 46 years (range 25-68). The median duration of symptoms was 6.8 months (range 3-12) months. The median duration of follow up was 16 months. We had 8 females, and 4 males. Three patients were asymptomatic, but they had progressive enlargement of spleen over one month. The most common symptoms were malaise and abdominal pain, seen in 8 patients. The other less frequent symptoms were fever (5 patients), weight loss (5 patients), arthralgia (4 patients), while the bleeding manifestation was seen in one patient only. Anemia was seen in 5 patients, two had leucopenia, and two had thrombocytopenia. Focal lesions in the spleen were seen in two patients by ultrasound and CT scan. The results of bone marrow aspirate and biopsy, upper gastrointestinal endoscopy and serological tests for collagen vascular diseases all were unrevealing prior to splenectomy. The histopathological results were; Hodgkin disease(1 patient), intermediate grade Non-Hodgkin lymphoma(1 patient) , splenic marginal zone NHL(2 patients),Diffuse Large B Cell Lymphoma(1 patient), Gaucher’s disease(1 patient), favor myeloproliferative disorders(1 patients), one patient had tuberculosis, while 4 patients ended with non-diagnostic results. Laproscopic splenectomy was done in one patient only. Postoperative complications were seen in 4 patients which were grade 1-2 bleeding and simple wound infection. During follow up one patient with undiagnostic reports proved to have collagen vascular disease & two patients developed lymphoma, and the last one developed features of myeloproliferative disorder. Conclusion: splenectomy for isolated splenomegaly has a significant impact on the management of a significant proportion of those 12 patients. Other investigations which help in the diagnosis of collagen vascular diseases, myeloproliferative disorders& lymphoproliferative disorders are needed before proceeding for splenectomy.